Effect of PGRs on growth, reproductive efficiency, and quality of tomato (Solanum lycopersicum L.) in arid regions (Current Horticulture, 2024)
An experiment was conducted during rabi, 2021-22 at College of Agriculture, Jodhpur to assess the effect of plant growth  regulators (PGRs) on the growth, flowering, and fruiting characteristics; and quality of tomato (Solanum lycopersicum L.) in a  randomized block design with three replications comprising 10 treatments. Three levels each of GA3, 4-CPA, and NAA along  with control were used. There was maximum plant height (47.2 cm, 61.3 cm, and 80.9 cm at 45 DAT, 60 DAT, and final harvesting,  respectively), number of branches (19.4/plant), leaf area (30.6 cm2), TSS (5.41˚Brix) and ascorbic acid (22.8 mg/100g) over the  control with GA3@75 ppm, whereas minimum acidity (0.46 %) was recorded with NAA@75 ppm. The significantly higher fruit  length (6.7 cm), fruit diameter (7.2cm), and fruit firmness (2.6 kg/cm2) were recorded with 4-CPA@75 ppm. The maximum  number of fruit clusters (12.0/plant), number of flowers (5.4/cluster), number of fruits (3.2/cluster), number of fruits (38.1/plant),  fruit setting (59.7%), fruit weight (84.3 g) and lycopene content (6.5 mg/100g) were observed with NAA@75 ppm.
Keywords: 4-Chlorophenoxy acetic acid; flowering; fruiting; gibberellic acid; naphthalene acetic acid